Emerging contaminants and nutrients synergistically affect the spread of class 1 integron-integrase (intI1) and sul1 genes within stable streambed bacterial communities. (1st July 2018) - Subirats, Jèssica; Timoner, Xisca; Sànchez-Melsió, Alexandre; Balcázar, José Luis; Acuña, Vicenç; Sabater, Sergi; Borrego, Carles M.
Abstract: Wastewater effluents increase the nutrient load of receiving streams while introducing a myriad of anthropogenic chemical pollutants that challenge the resident aquatic (micro)biota. Disentangling the effects of both kind of stressors and their potential interaction on the dissemination of antibiotic resistance genes in bacterial communities requires highly controlled manipulative experiments. In this work, we investigated the effects of a combined regime of nutrients (at low, medium and high concentrations) and a mixture of emerging contaminants (ciproﬂoxacin, erythromycin, sulfamethoxazole, diclofenac, and methylparaben) on the bacterial composition, abundance and antibiotic resistance profile of biofilms grown in artificial streams. In particular, we investigated the effect of this combined stress on genes encoding resistance to ciprofloxacin ( qnrS ), erythromycin ( ermB ), sulfamethoxazole ( sul1 and sul2 ) as well as the class 1 integron-integrase gene ( intI1 ). Only genes conferring resistance to sulfonamides ( sul1 and sul2 ) and intI1 gene were detected in all treatments during the study period. Besides, bacterial communities exposed to emerging contaminants showed higher copy numbers of sul1 and intI1 genes than those not exposed, whereas nutrient amendments did not affect their abundance. However, bacterial communities exposed to both emerging contaminants and a high nutrient concentration (1, 25 and 1 mg L −1 of phosphate, nitrate and ammonium, respectively) showed the highest increase on the abundance of sul1 and intI1 genes thus suggesting a factors synergistic effect of both stressors. Since none of the treatments caused a significant change on the composition of bacterial communities, the enrichment of sul1 and intI1 genes within the community was caused by their dissemination under the combined pressure exerted by nutrients and emerging contaminants. To the best of our knowledge, this is the first study demonstrating the contribution of nutrients on the maintenance and spread of antibiotic resistance genes in streambed biofilms under controlled conditions. Our results also highlight that nutrients could enhance the effect of emerging contaminants on the dissemination of antibiotic resistance. Graphical abstract: Image 1 Highlights: Emerging contaminants favor the spread of genes intI1 and sul1 in streambed biofilms. Emerging contaminants and nutrients synergistically affect the spread of these genes. Nutrients and pollutants did not change the biofilm bacterial composition.